Analysis of Halal Brand Image, Perceived Quality, And Brand Satisfaction On Wardah Consumer Purchase Intention - Septyarini, Ermaya Harni; Sekarsari, Larasati Ayu (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Purpose: This study analyzes the effects of Halal Brand Image, Perceived Brand Quality, and Halal Brand Satisfaction on consumer purchase intention for Wardah products in Indonesia. Methodology: A quantitative survey method was used, with data collected through questionnaires distributed to Wardah product users. Structural Equation Modeling (SEM) with WarpPLS 7.0 was applied to test the relationships between variables. Results: The findings reveal that Halal Brand Image, Perceived Brand Quality, and Halal Brand Satisfaction significantly influence consumer purchase intention for Wardah products. Findings: The study highlights the critical role of maintaining a strong halal brand image, improving perceived quality, and fostering satisfaction to drive consumer interest in halal cosmetics. Originality: This study contributes to the literature on purchase intention for halal cosmetics in the Indonesian market, addressing gaps in understanding these variables. Novelty: The research explores the interplay between branding, perceived quality, and satisfaction in the halal cosmetics context. Conclusions: Practical insights are offered to Wardah and similar brands to craft effective marketing strategies that align with consumer expectations in the halal cosmetics industry. Type of Paper: Survey-based quantitative research paper.